The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1182/blood-2015-03-636761
|View full text |Cite
|
Sign up to set email alerts
|

Acylcarnitines are anticoagulants that inhibit factor Xa and are reduced in venous thrombosis, based on metabolomics data

Abstract: • Untargeted and targeted metabolomics showed association of low plasma acylcarnitines levels with venous thrombosis risk.• Long-chain acylcarnitines are anticoagulants that inhibit factor Xa by binding to factor Xa outside the g-carboxy glutamic acid domain.In many patients with deep vein thrombosis and pulmonary embolism (venous thromboembolism, VTE), biomarkers or genetic risk factors have not been identified. To discover novel plasma metabolites associated with VTE risk, we employed liquid chromatography-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 26 publications
4
62
0
Order By: Relevance
“…A variety of minor abundance soluble plasma lipids manifest either procoagulant or anticoagulant properties by affecting thrombin generation (Figure 2A). Biochemical studies of plasma lipids and thrombin generation show that functionally important lipid binding sites are located on factor Xa outside its N-terminal Gla-domain 32,33 (Factor 2B) which historically has been to only region on factor Xa widely accepted to bind lipids. Thus, the canonical paradigm for clot- Table S2) might act to regulate inflammatory events such as cell proliferation at the same time they act to alter thrombin generation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A variety of minor abundance soluble plasma lipids manifest either procoagulant or anticoagulant properties by affecting thrombin generation (Figure 2A). Biochemical studies of plasma lipids and thrombin generation show that functionally important lipid binding sites are located on factor Xa outside its N-terminal Gla-domain 32,33 (Factor 2B) which historically has been to only region on factor Xa widely accepted to bind lipids. Thus, the canonical paradigm for clot- Table S2) might act to regulate inflammatory events such as cell proliferation at the same time they act to alter thrombin generation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that challenged the widely accepted, simple paradigm for PL‐Gla‐domain lipid effects on prothrombinase structure and activity involved synthetic, soluble dicaproyl‐PS that was reported to promote prothrombinase activity by binding to factor Xa outside the Gla‐domain (Figure B) . Similarly, recent publications both extend and challenge the simple classical paradigm for PL‐Gla‐domain‐factor Xa interactions because it was shown that several plasma lipids carried by lipoproteins or proteins such as albumin and/or lipid binding proteins (e.g, sphingosine, sphinganine, acyl‐carnitines [ACs], and lyso‐sulfatide [LSF]), so called “soluble” lipids, bind factor Xa and alter its procoagulant activity (Figure B), supporting and extending the challenge of the classical, simple paradigm for lipid‐clotting factor interactions. In summary, innovative findings show that certain, minor abundance plasma lipids can bind directly to factor Xa outside the Gla domain and modulate thrombin generation by the prothrombinase complex (Figure B), leading to an expanded framework for the paradigm for lipid‐clotting factor interactions …”
Section: Thrombosis Blood Coagulation and Thrombin Generationmentioning
confidence: 99%
See 3 more Smart Citations